Pengaruh Suasana Kerja dan Konflik Interpersonal terhadap Kinerja Karyawan di Dinas Kependudukan dan Pencatatan Sipil Surakarta - Muhammad Zulfikar R; Indra Hastuti; Esti Dwi Rahmawati (Universitas Maritim AMNI Semarang, 2024)
This study aims to analyze the effect of work atmosphere and interpersonal conflict on employee performance at the Surakarta City Population and Civil Registration Office (Dukcapil). The research population includes all employees of Dukcapil Surakarta, totaling 74 people. The variables studied include work atmosphere, interpersonal conflict, and employee performance. Data collection was conducted through a combination of primary and secondary data. Primary data collection methods used interviews and questionnaires, while secondary data were obtained through documentation. Data analysis used Structural Equation Modeling method with Partial Least Squares (SEM-PLS) approach, and data processing was done using SmartPLS software. The results showed that. Interpersonal conflict and work atmosphere are proven to have a significant impact on the performance of employees of the Surakarta City Dukcapil Office.